Fertility and milk yield characteristics in white Karaman and Chios x White Karaman (F1) crossbred sheep - Esen, F; Özbey, O (Scientific Technical Research Council Turkey, 2002)
In this study, various characteristics of fertility and milk yield were investigated in White Karaman and Chios x White Karaman crossbred (F-1) sheep. The study was carried out at the Research and Practice Farm at the University of Firat, on 30 White Karaman and 22 Chios x White Karaman crossbred (F-1) sheep 1.5 years of age to examine fertility characteristics and on 20 animals from each genotype at the age of 2 years to examine milk yield characteristics. Animals in oestrous cycle were improved by addition of a teaser ram within the study population, and they were then inseminated by previously selected rams. During the insemination, all the sheep were fed with alfalfa hay ad libitum in addition to pasturing. During the parturition season and lactation period, 600 g of concentrated feed were given for each animal in addition to alfalfa hay. In the study, pregnancy rates of 90% and 95% were determined in pure White Karaman and Chios x White Karaman crossbred (F-1) sheep, respectively. The proportions of sheep having parturition were 80% and 90% in the purebred and crossbred groups, respectively. Twin birth rate, average lamb number at each parturition and the proportion of lamb number at weaning were found as 16% and 40% (P<0.01), 1.6 and 1.40 (p<0.05) and 90% and 109% (P<0.05) in purebred and crossbred groups, respectively. Daily milk yield and lactation milk yield were 492.5, 510, 492.5, 362.5, 135 g and 14.13, 29.14, 44.30, 54.95, 63.58 kg for White Karaman; 932.50, 965.00, 991.75, 605.00, 332.50 g and 26.81, 55.82, 85.19, 105,18, 123.96 kg for Chios x White Karannan (F1) crossbreds on the 30th, 60th, 90th, 120th and 165th days of lactation, respectively. Lactation length and milk fat rate in White Karaman and Chios x White Karaman (F-1) crossbreds were 149.37 days and 6.37%: 158.65 days and 4.81%, respectively. Daily milk yield reached the peak point on 75th day of lactation for White Karaman and on the 90th day of lactation for Chios x White Karaman (F-1) crossbreds.
Akkaraman, sakiz x akkaraman melez (F1) koyunlarda döl ve süt verim özellikleri
Keywords: ewe; White Karaman; Chios; crossbreeding; fertility; milk yield